Effect of mechanical treatments on rooting in cuttings of guava, lemon and pomegranate (Indian Journal of Arid Horticulture, 2025)
An attempt was made to determine the most effective mechanical treatments i.e. ringing and girdling in relation to upper & lower portion of shoot of guava, lemon and pomegranate. The results revealed that cuttings obtained from lower end portion of ringed branch (M2) promoted significantly better growth parameters, particularly number of sprout shoots (4.0), shoot length 120 days after planting (28.00.cm), number of leaves (45.66), length and width of leaves (8.03 cm and 3.24 cm), leaf area index (41.24 cm2) as well as better success of rooting percentage (80%) in lemon followed by pomegranate (78%). In case of crop response, lemon significantly responsed to cuttings made from lower end portion of ringed branch followed by pomegranate subjected to shoot and root characteristics.
Keywords: Mechanical; Cuttings; Ringing; Guava; Lemon; Pomegranate; Girdling